До хронології карбування монет Володимира Ольгердовича (1362—1394) - Козубовський, Г.А. (Археологія, 2016)
На основі датування скарбів, метрологічного та стилістичного аналізу запропоновано відносну хронологію київських монет XIV ст. Analysis of the finds made it possible to determine seven types of the 14th century Kyiv coins. Type I are represented by imitations of coins struck by Jani Beg (1342–1357), khan of Golden Horde, in Gulistan. The striking of this type is dated to the 1360s and 1370s. The obverse of type II contains a Cyrillic inscription and the Prince’s sign. On the reverse, there is an imitation of Horde’s Muhammad Bulak coin of 773 (1371/1372). Coins of this type are dated to the 1370s. Type III includes coins with the Prince’s sign and a plaiting with a legend containing the name of the Prince around it. They can be dated by the 1380s or probably by the early 1390s. Type IV includes the coins with the Prince’s sign and «IS» and a legend with the Prince’s name around it. They can be dated by the period from the end of the 1370s to the beginning of the 1390s. The coins of type V with the Prince’s sign and a cross with four points and with a legend containing the Prince’s name around it, as well as coins of type VI and VII, namely, bracteates with Prince’s sign or cross, are dated to the 1390s. Анализ находок дает возможность выделить семь типов киевских монет ХІV ст. Первый тип представлен подражаниями золотоордынских дирхемов монет Джанибека (1342—1357), чеканенных в Гюлистане. Чеканка этого типа датируется 1360—1370 гг. На аверсе монет второго типа присутствует легенда кириллицей и княжеский знак. На реверсе — подражание ордынской монете Мухаммеда Буляка 773 г.х. (1371/1372). Монеты этого типа датируются 1370-ми гг. Третий тип — монеты с княжеским знаком и плетенкой, вокруг которой помещена легенда с именем князя. Они могут датироваться 1380-ми гг., возможно началом 1390-х гг. Четвертый тип — монеты с княжеским знаком и «IS», вокруг которой находится легенда с именем князя. Они могут датироваться концом 1370-х — началом 1390-х гг. Монеты пятого типа — с княжеским знаком и крестом с точками, вокруг которой присутствует легенда с именем князя, и монеты шестого и седьмого типов — брактеаты с княжеским знаком и крестом, датируются 1390-ми гг.